PENGARUH MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TERHADAP KETERAMPILAN MENULIS TEKS BIOGRAFI - Putri, Irda Eka; Afnita, Afnita; Hafrison, Mohammad (Universitas Negeri Padang, 2018)
ABSTRACT The research is aimed (1) to describe ability of writing biographical texts of students grade X at SMA Negeri 7 Padang before using cooperative integrated reading and composition learning model, (2) to describe the ability of writing biographical texts of students grade X SMA Negeri 7 Padang after using cooperative integrated reading and composition leaning model, (3) to describe the effect of cooperative integrated reading and composition learning model to words the ability of writing biographical texts of students grade X at SMA Negeri 7 Padang. This is quantitative research combines with experimental method. Based on data analysis, the use of cooperative integrated reading and composition learning model influences the ability of writing biographical texts of students grade at SMA Negeri 7 Padang. Kata kunci: pengaruh, cooperative integrated reading and composition, teks biografi